STUDI LITERATUR: ANALISIS PENGGUNAAN POP-UP BOOK SEBAGAI MEDIA PEMBELAJARAN IPA SMP - Rahayu Ningtias; Firdha Yusmar; Rayendra Wahyu Bachtiar; Fauziyatul Iffah; Sri Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objective of this study is to examine the utilization of Pop-Up Book media in the context of learning Natural Sciences (IPA) at the junior high school (SMP) level. The methodology employed is a systematic literature review guided by the PRISMA approach, encompassing the identification, screening, eligibility, and inclusion of pertinent articles. A comprehensive review of the extant literature yielded seven articles that satisfied the established inclusion and exclusion criteria. These articles were then subjected to a rigorous analysis to address two primary research questions: (1) What materials are employed as topics in Pop-Up Books for science education, and (2) What aspects of learning are demonstrably enhanced by the utilization of Pop-Up Book media in science education at the junior high school level? The analysis indicates that the Pop-Up Book is an effective tool for enhancing students' cognitive, affective, and social dimensions. From a cognitive perspective, this media assists students in comprehending abstract scientific concepts through engaging three-dimensional visual representations. Within the affective domain, the Pop-Up Book has been demonstrated to cultivate students' interest and motivation to learn, while concurrently fostering curiosity and responsibility. From a sociological perspective, this medium fosters collaboration and communication among students engaged in learning activities. The utilization of Pop-Up Books in the context of science education in junior high school has been demonstrated to enhance comprehension of scientific concepts. Furthermore, it has been observed to foster creativity, refine critical thinking abilities, and fortify the affective and social dimensions of students. This multifaceted approach positions Pop-Up Books as an effective pedagogical tool.